MEMAHAMI PRAGMATIK LINTAS BUDAYA: MENJEMBATANI MAKNA DI TENGAH KEBERAGAMAN - Kalsum R, Ummu; Saleh , Muhammad (Almeera Education, 2025)
In the era of globalization, interactions among individuals from diverse cultural backgrounds have become inevitable. Effective communication in such contexts requires not only grammatical proficiency but also pragmatic competence—the ability to interpret implied meanings within utterances. This article explores the challenges and complexities of cross-cultural pragmatics by examining three key dimensions: meaning interpretation, variations in politeness norms, and differences in speech acts. Through this analysis, the paper highlights the critical role of cultural sensitivity in communication, emphasizing its importance in preventing misunderstandings and fostering harmonious interpersonal relationships.